Zhodnocení ekonomické situace podniku - Lattenbergová, Gabriela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce je zaměřena na zhodnocení ekonomické situace podniku GRANDE, s.r.o. v období 2018-2022. Zhodnocení podniku je provedeno pomocí strategické a finanční analýzy. V první části práce jsou vymezeny teoretické pojmy a metody analýz. V druhé části jsou pojmy a metody využity k praktickému zpracování analýzy podniku. Na základě provedené analýzy jsou následně vyhodnoceny doporučení ke zlepšení situace podniku a vymezeny jejich přínosy.

The bachelor thesis is focused on the evaluation of the economic situation of GRANDE, s.r.o. in the period of 2018-2022. The evaluation of the company is carried out by the means of strategic and financial analysis. The theoretical concepts and methods of analysis are defined in the first part of the thesis. In the second part, the concepts and methods are used for the practical analysis of the enterprise. Based on the analysis, recommendations for improving the situation of the enterprise are then evaluated and their benefits are defined.
Assessment of Economic Situation of the Company
Keywords: Strategická analýza; finanční analýza; účetní výkazy; silniční nákladní doprava; zadluženost; likvidita; rentabilita; Strategic analysis; financial analysis; financial statements; road freight transport; indebtedness; liquidity; profitability